IMPACT OF SERVICE QUALITY ON RESIDENTIAL SATISFACTION : A STUDY WITH SPECIAL ATTENTION TO CHENNAI - Chezhiyan, K. (International Journal of Research -GRANTHAALAYAH, 2021)
The purpose of this paper is to reveal the residential satisfaction of apartment residents. And it was measured through an antecedent (service quality) and a consequence (word of mouth) of residential satisfaction. Simple random sampling method was employed on 200 residents and multiple linear regressions were carried out. The result shows that 85% of the variance in overall customer satisfaction is accounted for by service quality. From the above findings it is clear that service quality positively influences customer satisfaction.